The triglyceride-glucose index associated with reduced risk of liver metastasis in pancreatic cancer - Taijun Yi; Taijun Yi; Zejin Lin; Zejin Lin; Ziyan Mai; Ziyan Mai; Yongling Liang; Yongling Liang; Chengrui Zhong; Chengrui Zhong; Xingyu Li; Xingyu Li; et al. (Frontiers in Endocrinology)
BackgroundThe triglyceride-glucose (TyG) index has emerged as a reliable surrogate marker for insulin resistance and is associated with multiple malignancies. However, its role in pancreatic cancer liver metastasis (PCLM) remains unclear. This study aimed to investigate the relationship between TyG index and PCLM and evaluate its predictive value for PCLM.MethodsThis study enrolled 172 patients diagnosed with pancreatic cancer at Sixth Affiliated Hospital of Sun Yat-sen University between 2021 and 2024. Both cross-sectional and longitudinal analyses were employed. Logistic regression, propensity score matching (PSM) and subgroup analysis were utilized to assess the relationship between TyG index and PCLM, and a predictive model was constructed. Kaplan-Meier curves and cox proportional hazards regression analysis were conducted to assess the impact on liver metastasis. LASSO regression and Firth regression were conducted to avoid over-fitting issue. Restricted cubic splines (RCS) were applied to explore the nonlinear relationship.ResultsA significant inverse association was observed between TyG index level and PCLM incidence. Both multivariate logistic and cox regression suggested that a lower TyG index is associated with an increased risk of PCLM. A nomogram model was established and possessed a moderate degree of predictive accuracy (AUC = 0.75, 95% CI = 0.67-0.82). Notably, similar conclusions were reached in the subgroup of pancreatic ductal adenocarcinoma.ConclusionComprehensive analysis suggest that higher TyG index level is associated with reduced risk for PCLM, offering significant guidance for the prediction and early intervention of PCLM.